Role of improving molybdenite flotation by using aromatic hydrocarbon collector in high-calcium water: A multiscale investigation. (January 2023) - Wan, He; Yi, Peng; Song, Xuewen; Luukkanen, Saija; Qu, Juanping; Yang, Wei; Li, Hui; Bu, Xianzhong
Graphical abstract: Highlights: AH as a co-collector improve molybdenite flotation recovery in high-calcium water. The interaction of AH with Mo atoms of MS100 relies on cation-π bonds. AH cannot interact with Ca 2+ on MS100 relying on cation-π bonds. AH can promote the adsorption of HO in MS100. Synergistic adsorption of AH and HO improves molybdenite surface properties. Abstract: The poor molybdenite flotation behavior in high-calcium water is mainly caused by the fact that Ca 2+ ions can inhibit the adsorption effect of hydrocarbon oils on the molybdenite surface. Eliminating the negative influence of Ca 2+ ions on molybdenite flotation is of great significance. In this work, aromatic hydrocarbon (AH) was selected as a synergistic collector to reduce the deleterious effect of Ca 2+ ions on the molybdenite flotation using hydrocarbon oils (HO) as the collector. Various methods including flotation tests, contact angle measurements, zeta potential, X-ray photoelectron spectroscopy (XPS), density functional theory (DFT), and molecular dynamics (MD) simulations were carried out to understand the adsorption behavior of AH on molybdenite surface and its synergistic mechanism with HO. The flotation results showed that AH as a synergistic collector could improve molybdenite flotation in high-calcium water. The zeta potential and contact angle measurements indicated AH can adsorb on molybdenite (1 0 0) surface (MS100), weaken the MS100 hydrophilicity, and promoted more HO adsorb on the MS100. The XPS showed that the adsorption is mainly physical adsorption. Moreover, DFT calculation results indicated that AH can form a cation-π bond with the Mo-atom of MS100. MS simulations results suggested that the adsorption of AH on the MS100 can enhance the adsorption of HO molecules in this environment, thus weakening the adverse influence of Ca 2+ ions on molybdenite flotation. The results provide a basis for understanding and improving the separation effect of molybdenite from other minerals in the presence of Ca 2+ ions.